2014
DOI: 10.1002/prca.201300014
|View full text |Cite
|
Sign up to set email alerts
|

ApoA‐I mutations, L202P and K131del, in HDL from heterozygotes with low HDL‐C

Abstract: Purpose Mutations in apolipoprotein A‐I (apoA‐I) may affect plasma high‐density lipoprotein (HDL) cholesterol levels and the risk for cardiovascular disease but little is known about the presence and effects of circulating apoA‐I variants. This study investigates whether the apoA‐I mutations, apoA‐IL202P and apoA‐IK131del, are present on plasma HDL particles derived from heterozygote carriers and whether this is associated to changes in HDL protein composition. Experimental design Plasma HDL of heterozygotes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Furthermore, such MS approaches are not only useful for PTMs but also of value to understand the impact of protein variations caused by genetic polymorphism. For example, a recent study of heterozygotes with an apoA-I mutation (K131Del) showed that, in contrast to what could be expected, the mutant protein was more abundantly expressed in HDL than the native protein (Ljunggren et al 2013). Herein four HDL proteins that are all expressed as different isoforms have been discussed: two (apoA-I and apoC-III) in which PTMs have been shown to be important for lipid metabolism and two (apoA-II and SAA) in which the role of PTMs is still unclear.…”
Section: Protein Isoforms Translational and Posttranslationalmentioning
confidence: 94%
“…Furthermore, such MS approaches are not only useful for PTMs but also of value to understand the impact of protein variations caused by genetic polymorphism. For example, a recent study of heterozygotes with an apoA-I mutation (K131Del) showed that, in contrast to what could be expected, the mutant protein was more abundantly expressed in HDL than the native protein (Ljunggren et al 2013). Herein four HDL proteins that are all expressed as different isoforms have been discussed: two (apoA-I and apoC-III) in which PTMs have been shown to be important for lipid metabolism and two (apoA-II and SAA) in which the role of PTMs is still unclear.…”
Section: Protein Isoforms Translational and Posttranslationalmentioning
confidence: 94%